2018
DOI: 10.1155/2018/1821359
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Cardiac Remodeling and Dysmetabolism by Pancreatic Islet Injury Improvement in Diabetic Rats after Yacon Leaf Extract Treatment

Abstract: Yacon (Smallanthus sonchifolius) is a native Andean plant rich in phenolic compounds, and its effects on dysmetabolism and cardiomyopathy in diabetic rats was evaluated. The rats (10/group) were allocated as follows: C, controls; C + Y, controls treated with Yacon leaf extract (YLE); DM, diabetic controls; and DM + Y, diabetic rats treated with YLE. Type 1 diabetes (T1DM) was induced by the administration of streptozotocin (STZ; 40 mg−1/kg body weight, single dose, i.p.), and treated groups received 100 mg/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 49 publications
0
6
0
1
Order By: Relevance
“…Aging increases TGF‐ß expression, which plays an important role in the synthesis and secretion of collagen by cardiac fibroblasts, thus contributing to cardiac stiffening (Nakou et al, ). Kaempferol and PC of a yacon plant were shown to alleviate, respectively, myocardial fibrosis in angiotensin II‐induced cardiac dysfunction and in diabetic rat model (Dos Santos et al, ; Liu et al, ). Nevertheless, these experiments were undergone in pathological conditions not related to normal aging.…”
Section: Discussionmentioning
confidence: 99%
“…Aging increases TGF‐ß expression, which plays an important role in the synthesis and secretion of collagen by cardiac fibroblasts, thus contributing to cardiac stiffening (Nakou et al, ). Kaempferol and PC of a yacon plant were shown to alleviate, respectively, myocardial fibrosis in angiotensin II‐induced cardiac dysfunction and in diabetic rat model (Dos Santos et al, ; Liu et al, ). Nevertheless, these experiments were undergone in pathological conditions not related to normal aging.…”
Section: Discussionmentioning
confidence: 99%
“…Yacon leaves have been traditionally used in the Andes to treat people suffering from diabetes and digestive diseases. In experimental trials, dos Santos et al [12,65] reported a significant reduction of glycemia, an increase in insulin concentration, and a decrease in serum triacylglycerol concentration in streptozotocin-induced diabetic rats after the oral administration of yacon leaf extract for 30 days. Valentova et al [66] and other studies [67,68,69,70] reported the anti-hyperglycemic effects of yacon leaf extract in animal models.…”
Section: Health Effects (Usually Benefits) Of Yacon and Its Bioactmentioning
confidence: 99%
“…Myocardial fibrosis is a major mechanism contributing to cardiomyocyte changes in diabetic cardiomyopathy [21,22]. Hyperglycemia induces formation of structural proteins and type 1 collagens, and promotes interstitial fibrosis and myocardial stiffness to produce subsequent heart failure [20].…”
Section: Resultsmentioning
confidence: 99%